Understanding the State Budget and Its Effect on Communities of Color: The Importance of Civic Participation in the Budget Process. - Durant, Deborah.; Henry, Meghan.; Lindgren, Kerstin.; Vernon, Audra. (Tufts University. Tisch Library., 2018)
2005 M.A. in Urban and Environmental Policy and Planning Field Project. Client: Union of Minority Neighborhoods.